Efeito do alumínio sobre a absorção e sobre o transporte de fósforo em dois cultivares de sorgo (Sorghum bicolor L Moench) - Cambraia, José; Gimenez Calbo , Adonai (Revista Ceres, 2025)
The effects of aluminum on the uptake and transport of radioactive phosphorus were studied in two cultivars of sorghum differing in their tolerance to aluminum.